Evidences of Reduced Antioxidant Activity in Patients With Chronic Migraine and Medication‐Overuse Headache. Issue 7 (30th June 2015) - Lucchesi, Cinzia; Baldacci, Filippo; Cafalli, Martina; Chico, Lucia; Lo Gerfo, Annalisa; Bonuccelli, Ubaldo; Siciliano, Gabriele; Gori, Sara
<x xml:space="preserve">Abstract</x> Background Migraine is a complex multifactorial, neurobiological disorder, whose pathogenesis is not fully understood, nor are the mechanisms associated with migraine transformation from episodic to chronic pattern. A possible role of impaired oxidative mitochondrial metabolism in migraine pathogenesis has been hypothesized, and increased levels of peripheral markers of oxidative stress have been reported in migraine patients, although the literature data are limited and heterogeneous. Objectives The aim of this cross‐sectional study was to determine plasmatic levels of advanced oxidation protein products, ferric‐reducing antioxidant power and total plasmatic thiol groups, all plasmatic markers related to oxidative stress, in a sample of chronic migraine patients and medication‐overuse headache, compared to a control group of healthy subjects. Methods Thirty‐three patients with a diagnosis of both chronic migraine and medication‐overuse headache (International Classification of Headache Disorders, 3rd edition, beta version) and 33 healthy, headache‐free subjects were enrolled. Patients with comorbid/coexisting conditions were excluded, as well as patients in treatment with migraine preventive drugs. Plasmatic levels of advanced oxidation protein products, ferric‐reducing antioxidant power, and total thiol groups were determined in migraine patients and controls; moreover, oxidative stress biomarkers were compared in migraine patients with triptan compared to non‐steroidal anti‐inflammatory drug overuse. Results The statistical analysis showed significantly lower levels of ferric‐reducing antioxidant power and total plasmatic thiol groups, both expression of antioxidant power, in patients with chronic migraine and medication‐overuse headache compared to controls (respectively, ferric antioxidant power median [interquartile range] 0.53 [0.22] vs 0.82 [0.11] mmol/L, P < .001; total thiol groups 0.25 [0.08] vs 0.51 [0.11] μmol/L, P < .001). Moreover, no statistically significant differences in oxidative stress biomarkers were detected between patients with triptan and nonsteroidal anti‐inflammatory drug overuse. Conclusions The data from the present study suggest that antioxidant capacity is lower in chronic migraine patients and medication‐overuse headache compared to healthy headache‐free subjects, with no differences between patients with triptan or nonsteroidal anti‐inflammatory drug overuse. Further investigation is certainly necessary in order to define the causal or consequential role of an imbalance between pro‐oxidants and antioxidant defenses in migraine pathogenesis and "chronification" and the possible therapeutic implications in clinical practice.